Arbuscular Mycorrhiza: Their distribution and association with plants in the revegetated mine spoils of India – an overview - Logaprabha, V; K. S., Tamilselvi (Research in Plant Biology, 2014)
Reclamation of mine spoils is receiving considerable attention in the recent years due to the ill effects of mining and dumping of the mine spoil waste leading to various environmental hazards. Mycorrhizal inoculation of mine spoils and mine spoil dumps is essential for the establishment of a diverse plant community and a better ecosystem. This review focuses on the status of AM fungi, their distribution, diversity and density in the various mine spoils and mine spoil dumps of India. Species belonging to the genus Glomus was found to be widely distributed among the mine spoils. Legumes were the dominant and tolerant plants of the mine spoils supporting mycorrhizal colonisation.